DEVELOPMENT OF HALAL TOURISM IN THE PERSPECTIVE OF PROVIDING HALAL RESTAURANTS - Peristiwo, Hadi (International Journal Mathla’ul Anwar of Halal Issues, 2024)
Halal tourism is a sector that is experiencing very rapid growth and is a contributor to foreign exchange in Indonesia. On the other hand, halal restaurants have an important role in fulfilling the food and drink needs of Muslim tourists who come to visit a halal tourism destination. Halal restaurants for the halal tourism sector must at least have criteria such as having a halal certificate to guarantee that food and drinks can be enjoyed or consumed by Muslim tourists who come to visit. The method used in this research is qualitative research with a descriptive approach. Based on the research results, it is concluded that the market potential for the halal restaurant industry in Indonesia is experiencing rapid development. Over the last few years, Indonesia has been ranked first as a consumer of halal food in the world. However, this huge market potential has not been able to be utilized optimally to improve the halal tourism sector. Maintaining the halal quality of food products (halal integrity) in halal restaurants is one way to compete in halal tourism with other countries